Proposed new design of Wellness Villa at Ulu Legong Hot Spring Recreational Park Ulu Legong, Mukim Siong, Baling, Kedah Darul Aman / Arita Hanim Awang - Awang, Arita Hanim (Faculty of Architecture, Planning and Surveying, 2005)
Wellness is a keyword for our times. From the old fashion notion of the cure, a world wide industry has develop with just one goal; the improvement of our well being; the creation of balance between body, spirit and soul. But only seldom are wellness programmed presented in conjunction with an aesthetic environment. It has been a trend for years ago in other foreign country that they specified some of their aesthetic environment or places to be the best wellness centre with many kind of natural wellness therapy. For example, Japan is well known for their mount of volcanoes and they manipulated it to make great wellness hotel with various natural therapy like spa, mud bathing, hot spring bathing etc. People who concern about their health would travel to find one perfect place to retreat their selves with special natural treatments. As the result, they manage to attract more tourists to their country and as everyone knows, tourism gives a lot of income for the country. Wellness hotel is a new term for resorts or hotel that provided special wellness treatment like spa, sauna, traditional massage, aromatherapy and many alternative therapies. These hotels and resort were usually visited for their facilities and treatment they provided. People come from all over the world to get treatments and at the same time enjoy the beautiful scenery at the resort. For my final project, I choose to propose new design of Wellness Villa at Ulu Legong Hot Spring, the biggest natural hot spring pool in peninsular Malaysia. The Wellness Villa which I proposed is a small scale of destination spa.